Przemoc i agresja u dzieci i młodzieży. O języku agresji - Sileńska, Aleksandra; Szpunar, Kamila (Człowiek i Społeczeństwo, 2020)
Aggression is defined as the intentional action which causes pain and injury. The actions of an aggressive nature are designed to cause physical or mental harm to another person (Aronson, Wilson, & Akert, 1997). In contrast, violence is defined as an intentional action that goes beyond social norms and causes mental or physical pain (Pospiszyl, 1999). The article is concentrated on aggressive and violent language among children and adolescents. The term of ”language of aggression” has not been precisely defined yet. The language of aggression occurs the most when negative emotions and intentions are involved in the communication (Majchrzyk, 2002). The language of aggression is not only about using specific bad words but also about the way we speak. The article presents an overview of Polish and foreign literature concerning the issue of the language of aggression in children and adolescents. It shows why do teenagers and children use aggressive language, how is defined term of ”aggressive language” and what specialists can do to prevent such kind of problem.